This question is missing crucial information. Specifically the mathematical operators... as in +, -, x, /,=... and so on. POSSIBLE INTERPRETATIONS OF QUESTION: 5x-3y=6 ---> SLOPE= 5/3 5x+3y=6 ---> SLOPE= -5/3 5x*3y=6 ---> SLOPE= Not Applicable (Rational Function) 5x/3y=6 ---> SLOPE= 5/18 5x=3y-6 ---> SLOPE= 5/3 5x=3y+6 ---> SLOPE= 5/3 5x=3y*6 ---> SLOPE= 5/18 5x=3y/6 ---> SLOPE= 10/1 I hope one of these worked.
the simplest form of 5x + 3y +2x - 6y is 7x-3y
(4, -7)
It is an algebraic expression that can be simplified to: 5x+9y+5
5x+3y is an algebraic expression in two terms
Slope = 5/3 = 1.66...
Oh, dude, it's like super simple. The terms of that expression are 5x, -3y, and 4. Each of those is a term because they're separated by those plus and minus signs. So, like, that's it.
To simplify the expression 5x - (-3x), you can rewrite it as 5x + 3x since subtracting a negative is the same as adding a positive. This simplifies to 8x. So, the result of 5x - (-3x) is 8x.
The one(s) where the y coordinate is:five times the x coordinate plus three;five times the x coordinate minus three;three plus five times the x coordinate; orthree minus five times the x coordinatedepending upon which of the following equations is intended (as there are missing operators in the question):y = 5x + 3y = 5x - 3y - 5x = 3y + 5x = 3[Note equations 1 & 3 are the same equation written in different forms.]
5x + (3y-x) + (10-2y) = 5x + 3y - x + 10 -2y = 5x - x + 3y - 2y + 10 = 4x + y +10
5x -3y = -6 -3y = -5x -6 y = 5/3x+2 in slope intercept form
This question is missing crucial information. Specifically the mathematical operators... as in +, -, x, /,=... and so on. POSSIBLE INTERPRETATIONS OF QUESTION: 5x-3y=6 ---> SLOPE= 5/3 5x+3y=6 ---> SLOPE= -5/3 5x*3y=6 ---> SLOPE= Not Applicable (Rational Function) 5x/3y=6 ---> SLOPE= 5/18 5x=3y-6 ---> SLOPE= 5/3 5x=3y+6 ---> SLOPE= 5/3 5x=3y*6 ---> SLOPE= 5/18 5x=3y/6 ---> SLOPE= 10/1 I hope one of these worked.
the simplest form of 5x + 3y +2x - 6y is 7x-3y
(4, -7)
-2x=2y-4 2x-y=-5 Answer=(-1,3)
If you mean: 5x+2y+x-3y then it is 6x-1y
It is an algebraic expression that can be simplified to: 5x+9y+5